A critical review of interactions between microplastics, microalgae and aquatic ecosystem function. (1st January 2021) - Nava, Veronica; Leoni, Barbara
Highlights: Studies about microplastics-microalgae interaction in aquatic systems were reviewed. Microalgae interact with microplastics affecting their density and fate. Microplastics have the potential to affect quality and quantity of algal production. Consequences on energy fluxes in aquatic food webs and on ecosystem functionalities. Need for further field-studies to address ecosystem implications. Abstract: With the widespread occurrence of microplastics in aquatic ecosystems having been firmly established, the focus of research has shifted towards the assessments of their influence on ecosystem functions and food webs. This includes interactions between microplastics and microalgae, as fundamental components at the base of aquatic food webs and pivotal organisms in a wide range of ecosystem functions. In this review, we present the current state of knowledge on microalgae–microplastic interactions and summarize the potential effect on their respective fate. Microplastics can and do interact with microalgae and the available literature has suggested that the epiplastic community of microalgae differs consistently from the surrounding aquatic communities; however, it is still not clear whether this different colonization is linked to the composition of the surface or more to the availability of a "hard" substrate on which organisms can attach and grow. Further studies are needed to understand to what extent the properties of different plastic materials and different environmental factors may affect the growth of microalgae on plastic debris. Biofouling may alter microplastic properties, especially increasing their density, consequently affecting the vertical fluxes of plastics. Moreover, microplastics may have toxic effects on microalgae, which could be physical or related to chemical interactions with plasticizers or other chemicals associated with plastics, with consequences for algal growth, photosynthetic activity, and morphology. Microplastics seems to have the potential to affect not only the quality (e.g., fatty acids and lipids composition, food dilution effect) but also the quantity of algal production, both positively and negatively. This may have consequences for energy fluxes, which may propagate throughout the whole food web and alter aquatic productivity. Even though experimental results have indicated reciprocal impacts between plastics and microalgae, it is currently difficult to predict how these impacts may manifest themselves at the ecosystem level. Therefore, further studies are needed to address this important topic. Graphical abstract: Image, graphical abstract